Ion interaction and hydrogen bonds as main features of protein thermostability in mutated T1 recombinant lipase originated from Geobacillus zalihae - Ishak, Siti Nor Hasmah; Ahmad Kamarudin, Nor Hafizah; Mohamad Ali, Mohd Shukuri; Thean, Adam Chor Leow; Raja Abd. Rahman, Raja Noor Zaliha (Multidisciplinary Digital Publishing Institute, 2020)
A comparative structure analysis between space- and an Earth-grown T1 recombinant lipase from Geobacillus zalihae had shown changes in the formation of hydrogen bonds and ion-pair interactions. Using the space-grown T1 lipase validated structure having incorporated said interactions, the recombinant T1 lipase was re-engineered to determine the changes brought by these interactions to the structure and stability of lipase. To understand the effects of mutation on T1 recombinant lipase, five mutants were developed from the structure of space-grown T1 lipase and biochemically characterized. The results demonstrate an increase in melting temperature up to 77.4 °C and 76.0 °C in E226D and D43E, respectively. Moreover, the mutated lipases D43E and E226D had additional hydrogen bonds and ion-pair interactions in their structures due to the improvement of stability, as observed in a longer half-life and an increased melting temperature. The biophysical study revealed differences in β-Sheet percentage between less stable (T118N) and other mutants. As a conclusion, the comparative analysis of the tertiary structure and specific residues associated with ion-pair interactions and hydrogen bonds could be significant in revealing the thermostability of an enzyme with industrial importance.